Dr. Jennifer Stark — Deep Plane Facelift — Westlake Village - Stark, Jennifer (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Jennifer Stark, practicing in Westlake Village, USA. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003245; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; usa; westlake village